Is Russia Restructuring? New Evidence on Job Creation and Destruction - Broadman, Harry G. (World Bank, Washington, DC, 2014)
The authors explore the labor dynamics of Russian enterprise restructuring, empirically assessing how patterns of job creation and destruction are related to various aspects of enterprise restructuring across firms in different sectors and regions, and to different forms, sizes, vintages, and performance characteristics of ownership. Evidence from case studies - based on more than 50 site visits in 2000 - suggests that jobs have been destroyed, but only to a limited degree in some sectors and regions, largely because of institutional and incentive constraints and a still-widespread "socialist" corporate culture. Jobs have been created - particularly in sectors where devaluation had the most pronounced effect on important substitution and export promotion - but only slowly, mostly for lack of skilled workers and because regional mobility is limited. Labor turnover appears higher within regions than across regions. Newly available data for 1996 - 99 (provided by Goskomstat) for about 128,000 enterprises in 24 industrial sectors in Russia's 89 regions indicates that the typical firm has experienced only modest downsizing - about 12 percent - in number of employees. Smaller firms have entered, and larger, mature businesses have exited some sectors. Except for a lull in 1998, the rate of job creation has steadily increased and the rate of job destruction has declined, dropping substantially in 1998 - 99. "Voluntary" worker separations remain the main - and growing - form of layoff, and the proportion of layoffs through redundancies is shrinking (now about 4 percent of total separations). Firm size and net employment growth are not statistically related, but form of ownership seems to matter. Firm size is also statistically correlated (positively) with profitability, but restructuring through changes in net employment growth appears not to be. It seems Russian restructuring needs to become more efficient.